THE EFFECT OF HUMAN RESOURCES AND INFORMATION TECHNOLOGY ON THE REVALUATION OF GOVERNMENT FIXED ASSETS - Indra, Indra (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2020)
The central government has implemented a government fixed asset revaluation policy. The main objective of the policy is to present the fair value of fixed assets in the government's financial statements. However, the results of fixed asset revaluation are not accepted by the BPK and must be corrected and recorded in the government financial statements for the 2019 fiscal year. Competent human resources and the use of information technology are considered two factors needed to achieve the revaluation objectives. This study was conducted to determine the level of significance of these two factors by distributing questionnaires to BMN officers and assessors from 82 ministries/agencies throughout Indonesia. The research data were processed by path analysis method using the Structural Equation Model (SEM) partial least squares (PLS) through Smart PLS 3.3.2 software used to assess measurement models and research structural models. The results of data processing concluded that the competence of human resources and information technology has a significant effect on the revaluation of government fixed assets. However, information technology needs to be improved again because the significance value is only half that of the human resources competency value.